Mesoporous Silica-Supported Sulfonyldiamine Ligand for Microwave-Assisted Transfer Hydrogenation - Sarkar, Shaheen M.; Md. Eaqub, Ali; Islam, Md. Shahrul; Lutfor, M. R.; Rashid, S. S.; Karim, Md. Rezaul; M. M., Yusoff (Hindawi Publishing Corporation, 2015)
N-Sulfonyl-1,2-diamine ligands, derived from 1,2-diaminocyclohexane and 1,2-diaminopropane, were immobilized onto mesoporous SBA-15 silica. The SBA-15-supported sulfonyldiamine-Ru complex was prepared in situ under microwave heating at 60 W for 3 min. The prepared sulfonyldiamine-Ru complex was used as an efficient catalyst for the transfer hydrogenation of ketones to the corresponding secondary alcohols. The heterogeneous complex showed extremely high catalytic activity with 99% conversion rate under microwave heating condition. The complexes were regenerated by simple filtration and reused two times without significant loss of activity.